Impact of Mobile Legends Game on Youth Procrastination - Mochamad Saputra Oetomo; Eni Fariyatul Fahyuni (Indonesian Journal of Cultural and Community Development, 2022)
Mobile Legends is an internet network-based game and is also popular in Indonesia. Academic procrastination is a tendency to delay starting or completing work as a whole. The purpose of this study was to determine the use of Mobile Legend games among adolescents in Jambangan Village and to determine the impact of Mobile Legends games on adolescent procrastination in Jambangan Village. The purpose of this research is to find out the use of Mobile Legends games among teenagers in Jambangan Village and to find out the impact of Mobile Legends games on adolescent procrastination in Jambangan Village. This study used qualitative research methods. The data collection techniques used are observation, interviews and documentation. The results of this study found that the use of the Mobile Legends game can be seen from (1) addiction, (2) requiring refreshment to relieve stress, (3) following trends that are emerging in the surrounding environment, (4) there is curiosity from within them. the impact of the Mobile Legends game can have an impact on adolescent procrastination, being lazy to study, school assignments being delayed and piling up, not being on time to do it, often neglecting assignments, delaying worship time. As for there are other impacts from the negative and positive sides, among others: often say dirty, wasteful and can improve English.